ADAPTATION AND MITIGATION OF CLIMATE CHANGE IN MAINTAINING FOOD SECURITY BY TRADITIONAL COMMUNITIES - Gemilang Lara UTAMA; Roostita L. BALIA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Ongoing climate change has affected individuals' lives in different parts of the world including the traditional communities. The accessibility of natural resources regularly utilized as a wellspring of occupation is so vulnerable against climate change. Alongside the event of an unnatural weather change that brought about outrageous climate change, different regular marvels that happen presently isn't the same any longer. Traditional communities may not comprehend the ideas of a global warming and climate change, yet they watch and feel their impact. Different saw impacts, for example, diminished precipitation, increment in air temperature, expanding the force of the sun and precipitation which isn't balanced out. Mostly food production is declining alongside different climatic changes. In a few simulation of climate change demonstrates of synthetic manure utilization, heat stress and water shortage can prompt a decrease in rice production up to 3.8% in Asia toward the finish of the 21st century. Adjustment and relief to climate change are done with different acclimations to decrease vulnerability or increase resilience to the climate change. Oblivious adaptation and mitigation practices of climate change have been honed by traditional communities through the cultivating frameworks they work. Different systems are completed not exclusively to address nourishment issues and to support their lives. Different discoveries demonstrate that the conventional cultivating framework keep running by the group is plainly ready to keep up their food security in the midst of the danger of dry season, heat stress and different interruptions caused by climate change.